2015
DOI: 10.4103/1658-354x.154706
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of intravenous infusion of N-acetylcysteine in cirrhotic patients undergoing major abdominal surgeries

Abstract: Background:Postoperative acute kidney injury (AKI) is common in patients with chronic liver disease. We prospectively evaluated effectiveness of the N-acetylcysteine (NAC) in preserving postoperative renal functions in cirrhotic patients undergoing major abdominal surgeries.Materials and Methods:A total of 60 cirrhotic patients child A to B were randomized into two groups of 30 each. NAC groupwas received intravenous infusion of NAC (1200 mg/12h starting immediately before surgery and continued for 72h h posto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
1
3
1
Order By: Relevance
“…17,20 However, others reported a shorter hospital stay after surgery in NAC-supplemented groups. 12 The results of our study showed shorter hospital stays in the study group than the control, but the difference was not statistically significant. The current study has several limitations, including the small sample size, short duration of NAC administration, and short period of patient follow up.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…17,20 However, others reported a shorter hospital stay after surgery in NAC-supplemented groups. 12 The results of our study showed shorter hospital stays in the study group than the control, but the difference was not statistically significant. The current study has several limitations, including the small sample size, short duration of NAC administration, and short period of patient follow up.…”
Section: Discussioncontrasting
confidence: 61%
“…Venous blood samples were obtained before surgery (baseline laboratory evaluation), and on day two after surgery as in previous studies that made the postoperative evaluations between 1 hour to 72 hours after surgery. 11,12…”
Section: Methodsmentioning
confidence: 99%
“…Ibrahim et al . [ 25 ] in their study found similar results and demonstrated that liver functions were well preserved with the administration of NAC to their study group of cirrhotic patients undergoing major abdominal surgery. In other different types of surgeries as laparoscopic, Beyaz et al .…”
Section: Discussionsupporting
confidence: 57%
“…Ibrahim et al . [ 25 ] demonstrated that NAC preserved postoperative renal function in cirrhotic patients undergoing major abdominal surgeries assessed by cystatin C concentration and cystatin C glomerular filtration rate. However, in our RCT, no significant difference was observed in serum creatinine between both groups.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Ibrahim and Sharawy, the effect of intravenous infusion of N-acetyl cysteine in cirrhotic patients undergoing abdominal surgery was investigated. Finally, it was shown that this intervention has led to the maintenance of liver and kidney function in these patients (21).…”
Section: Discussionmentioning
confidence: 97%